(untitled) - Diebold, Francis X. (Mason, OH., 2007)
This book focuses on the core techniques of widest applicability. The author illustrates all methods with detailed real-world applications, many of them international in flavor, designed to mimic typical forecasting situations
Keywords: Forecasting, Forecasting; Statistical methods,Problems, exercises, etc